2017
DOI: 10.1590/1806-9282.63.01.35
|View full text |Cite
|
Sign up to set email alerts
|

Factors related to non-adherence to mammography in a city of the Brazilian Amazonian area: A population-based study

Abstract: Objective: To assess the prevalence of mammography use and factors related to non-adherence in Boa Vista, capital of Roraima, Brazil. Method: A cross sectional study, quantitative analysis, based on household survey was performed between June and August 2013, using a face-to-face interview with a pre-tested form. Target population was women between 40 and 69 years. The sample size target was 240 participants, and the sampling method was random cluster sampling. The study was approved by the Institutional Revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 28 publications
0
22
0
1
Order By: Relevance
“…Most studies found an association between education levels and participation in mammography in the previous 1–3 years. [19, 23, 31, 3436, 39] Less clear associations were found in a study in Brazil [23] that only found primary education to be a determinant for participating in mammography; in another study in Costa Rica,[24] education negatively correlated with yearly participation in mammography, although not when the interval was set at three years. This study concluded that better-educated women tend to wait longer between mammography and Pap smear screenings than their less educated counterparts.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Most studies found an association between education levels and participation in mammography in the previous 1–3 years. [19, 23, 31, 3436, 39] Less clear associations were found in a study in Brazil [23] that only found primary education to be a determinant for participating in mammography; in another study in Costa Rica,[24] education negatively correlated with yearly participation in mammography, although not when the interval was set at three years. This study concluded that better-educated women tend to wait longer between mammography and Pap smear screenings than their less educated counterparts.…”
Section: Resultsmentioning
confidence: 93%
“…Most studies defined education level as number of years of schooling. [14, 1620, 24, 26, 27, 30, 35, 36] A few studies defined the level of education as the completion of primary, secondary or tertiary education,[21–23, 33] which makes regional comparisons more difficult.…”
Section: Resultsmentioning
confidence: 99%
“…In recent studies from various countries, high educational level was one of the most important predictors of adherence to MS. [28][29][30][31] In agreement with our results, several Brazilian studies reported a greater chance of adherence to MS among women with higher educational levels. 5,8,27,32,33 In contrast, a recent study also performed in the Northeast region of Brazil, among women who had predominantly a low educational level, high income instead of education was associated with MS participation. 9 The nationwide adherence study by Narayan et al in the United States identified both high income and educational level as important predictors of adherence to MS. 29 Data of the present study also indicated that occupied women performed MS more often compared with those who were not occupied.…”
Section: Discussionmentioning
confidence: 90%
“…In South Africa, 94.7% of the participants never used any breast cancer screening methods (36). In under-developed countries, the participation rate is almost the same as Iran: 75% of women over 40 in Turkey (37), 76.9% in Taiwan (38), 56% in Singapore (39), and 69.1% in Qatar (40) had no experience of mammography, and in Brazil 55.6% have not performed mammography in the past two years (41). On the other hand, the participation rate is higher in the developed countries: 85% of women aged 50-70 in Greece, 59.9% of Japanese women aged 40-70 (2), and 65.9% of African women aged 50-74 residing in Australia have performed mammography every two years and only 19% of them did not undergo mammograms (42).…”
mentioning
confidence: 99%